IMMUNE-INFLAMMATORY MARKERS of CHRONIC PYELONEPHRITIS - V. I. Nikulicheva; G. S. Safuanova; N. S. Karpina; T. Y. Lekhmus; D. R. Vagapova; S. V. Alonova (Acta Biomedica Scientifica, 2014)
The article presents the result of the detection of different-level inflammatory factors of immune defense in patients with chronic pyelonephritis (CP) with detection of definite interconnections between these factors and estimation of their significance in the chronification of the process. The absence of adequate effector reaction on the chronic inflammation with considerable (p < 0,05-0,001) depression of the phagocytosis system, decrease of stimulated reaction of blast-transformed lymphocytes, CD4-helpers, CD16-cells, cytotoxic lymphocytes (CD8), B-lymphocytes (CD22) with oppression of especially secondary immune response against the background of visible (p < 0,05-0,001) decrease of contents of activated lymphocytes (CD25), apoptosis receptors (CD95), antigene of main complex of histocompatibility of 11 class HLADR+, adhesive molecules ICAM-3 and proinflammatory cytokines IL-1β, IL-6, IL-8, ФНО-α was determined. The character of determined changes in the contents of immune-inflammatory markers that reflect different levels of immune system functioning points at profound disorders of effector reaction with significant oppression of recognition function and destruction by immune system of both endogenous and exogenous antigens and evident inconsistency of cytokines regulatory system in CP patients.